Geomedia networked cities and the future of public space - McQuire, Scott (Polity Press, 2016)
Geomedia offers critical analysis of the new possibilities and power relations emerging in the public space of contemporary cities. As ubiquitous digital networks enable embedded and mobile devices to integrate place-specific data with real-time feedback circuits, everyday experience of public space has become subject to new demands.